Modern Traditions: reconfigurations of school mathematics in the 1960s Tradições Modernas: reconfigurações da matemática escolar nos anos 1960 - Elizabete Zardo Búrigo (Universidade Estadual Paulista, 2010)
Regarding school curricula as social constructions, in this paper we analyze the building up of a tradition, which goes back to the 1960s, related to the introduction of Algebra in elementary school. This tradition is presented as an inheritance of the modern mathematics movement and it is argued that the analysis of curricular innovation processes should not take into account only their proclaimed purposes, but should consider broader effects related to the breakdown of older traditions. Keywords: History of Mathematics Education. Curriculum. Modern Mathematics. Teaching of Algebra. Na linha dos estudos que investigam os currículos escolares como construções sociais, este artigo examina a constituição de uma tradição relativa à iniciação em Álgebra na escola, cuja origem remonta aos anos 1960. Ao apresentar essa tradição como uma herança do movimento da matemática moderna, argumenta que os processos de inovação curricular não devem ser analisados apenas no confronto com suas intenções anunciadas, mas pelos efeitos mais amplos que produzem de desconstituição das tradições mais antigas. Palavras-chave: História da Educação Matemática. Currículo. Matemática Moderna. Ensino de Álgebra.